Places Revisited: Transnational Families and Stories of Belonging - Siim, Pihla Maria (Estonian Literary Museum, the Estonian National Museum and the University of Tartu, 2023)
Drawing on fieldwork material, the following article seeks to explore the ways members of transnational families create, maintain and negotiate relations to multiple places. People are not only shaped by the places in their lives, but they also employ different strategies to make a place feel like home. This repositioning is a constant process, affected also by the surrounding societal and cultural context. The choices to stay or to move have to be justified not only to oneself, but also to others (relatives and wider society). While doing this, people have to be more explicit about their relations to different locations, to put into words the feelings they have towards certain places. In this article, I concentrate on the emotional and social side of peoples’ place-related experiences.The article is based on interview material I have collected for my PhD dissertation in folklore. Interviews were made with immigrants from the former Soviet Union living in Finland and their family members living in the country of origin (in Russian Karelia and Estonia). The aim is to capture the experiences of both family members relocating and those staying put, and to discuss the meaning of place in the identity formation of people living mobile or transnational lives.